Medytacja chrześcijańska instrumentem nowej ewangelizacji - Piasecki, Piotr (Annales Missiologici Posnanienses, 2019)
The proclamation of the Gospel as Good news for all men has always been at the heart of the life of the mission of the Church. This is why the new evangelization in no way modifies the content of the Gospel, the message of salvation brought by Christ. But in the current global context, it is made ever more urgent and necessary. Faced with all these new phenomena that permeate the contemporary world and the Church, renewed enthusiasm and enthusiasm is needed to respond to the urgency and the need for a new evangelization. This inner impulse can only be the result of a rich and singular personal spirituality, without which the evangelizer runs the risk of quickly becoming exhausted or discouraged: Missionary activity requires a specific spirituality which concerns in particular those whom God has called missionaries (RMis 87). This specific spirituality is nourished by the meditation of Christ the Savior - the Word of God. Through this meditation, the new evangelizers experience being healed by God through Jesus Christ. The encounter with the living God is an entirely original, transformative experience that puts everything in its place and completely upsets reality. This results in the ardor of evangelization that is constantly renewed. All evangelization requires from those who announce, a testimony of life that attests to the truth and the reality of the Gospel. To give one's testimony on mission is to give an account of what we have lived, seen and heard, and meditation is a good way to carry out this reality. Evangelization has a mystical origin; it is a gift that comes from the cross of Christ the Savior. That is why Christian meditation rooted in the tradition of the Church - especially in the Gospel - is a means for the new evangelization.